Akreditasi Madrasah Aliyah dalam kebijakan Pendiknas - Ikhwan, Afiful (e-Journal STAI Muhammadiyah Tulungagung, 2014)
Accreditation is a small boomerang for the manager in improving the quality of education if the quality of the legal juridical madrasah be an internal conflict in the external even hit the target quantity instead of quality and customer satisfaction neglect veiled on mutualism occurs in the transaction value of education in madrasah, not too much to said that the accreditation madrasah / school can be angled in marketable education that leads to the money, who gets the profit is the demand in the market of education, and the